3,4‐Dimethoxychalcone induces autophagy through activation of the transcription factors TFE3 and TFEB - Guo Chen; Wei Xie; Jihoon Nah; Allan Sauvat; Peng Liu; Federico Pietrocola; Valentina Sica; Didac Carmona‐Gutierrez; Andreas Zimmermann; Tobias Pendl; Jelena Tadic; Martina Bergmann; et al. (EMBO Molecular Medicine)
Abstract Caloric restriction mimetics (CRMs) are natural or synthetic compounds that mimic the health‐promoting and longevity‐extending effects of caloric restriction. CRMs provoke the deacetylation of cellular proteins coupled to an increase in autophagic flux in the absence of toxicity. Here, we report the identification of a novel candidate CRM, namely 3,4‐dimethoxychalcone (3,4‐DC), among a library of polyphenols. When added to several different human cell lines, 3,4‐DC induced the deacetylation of cytoplasmic proteins and stimulated autophagic flux. At difference with other well‐characterized CRMs, 3,4‐DC, however, required transcription factor EB (TFEB)‐ and E3 (TFE3)‐dependent gene transcription and mRNA translation to trigger autophagy. 3,4‐DC stimulated the translocation of TFEB and TFE3 into nuclei both in vitro and in vivo, in hepatocytes and cardiomyocytes. 3,4‐DC induced autophagy in vitro and in mouse organs, mediated autophagy‐dependent cardioprotective effects, and improved the efficacy of anticancer chemotherapy in vivo. Altogether, our results suggest that 3,4‐DC is a novel CRM with a previously unrecognized mode of action.